Arming Anti-EGFRvIII CAR-T With TGFβ Trap Improves Antitumor Efficacy in Glioma Mouse Models - Li, You; Wu, Huifang; Chen, Gang; Wei, Xiaofan; Wang, Chunyu; Zhou, Shanshan; Huang, Ailing; Zhang, Zui; Zhan, Changyou; Wu, Yanling; Ying, Tianlei (Frontiers in Oncology, 2020)
Glioblastoma (GBM) is an aggressive malignancy with poor prognosis. New treatment and therapy strategy for GBM are urgently needed. Although clinical studies have demonstrated the feasibility and safety of chimeric antigen receptor (CAR) T cell therapy for GBM, the efficacy have not been that impressive. The major limit for anti-tumor efficacy of CAR-Ts is immunosuppressive milieu of GBM tumor microenvironment (TME). TGFβ, a substantial component in GBM, compromises immune response and contributes to the immune evasion and tumor progression. To overcome the limitation and improve the efficacy of CAR-T cells for GBM, we optimized the EGFRvIII-specific CAR construct with TGFRII ectodomain as a TGFβ-trap and generated TGFβ-resistant CAR-Ts for GBM therapy. We demonstrated that this TGFβ-trapped architecture enhanced anti-tumor efficacy of EGFRvIII-specific CAR-T and prolonged the survival of mice bearing GBM. In addition, the GBM-infiltrated microglia, typically considered tumorigenic, showed increased expression of M1 polarization markers in TGFβ-trap CAR-Ts group, indicating that these microglia were polarized towards pro-inflammatory and anti-tumorigenic phenotype. Overall, these results indicated that arming with TGFβ-trap and diminishing the immunosuppressive effect is a potential strategy to improve CAR-T efficacy for GBM therapy.